Ferrocenylvinyl-flavones: Synthesis, structure, anticancer and antibacterial activity studies - Kowalski, Konrad; Koceva-Chyla, Aneta; Szczupak, Lukasz; Hikisz, Pawel; Bernasinska, Joanna; Rajnisz, Aleksandra; Solecka, Jolanta; Therrien, Bruno (My University, 2013)
Four new ferrocenylvinylflavone complexes were obtained via Pd-catalyzed Heck cross-coupling reactions: (E)-6-ferrocenylvinyl-chromen-4-one (4), (E)-6-ferrocenylvinyl-2-methyl-chromen-4-one (5), (E)-6-ferrocenylvinyl-2-phenyl-chromen-4-one (6) and (E)-6-ferrocenylvinyl-chromen-4-one-3-propionic acid (7). All compds. were characterized by 1H NMR, 13C NMR, IR spectroscopy, high resoln.-MS, elemental anal. and cyclic voltammetry. The mol. structures of derivs. 4 and 6 were confirmed by x-ray crystallog. The biol. activity of the complexes was rationalized on the basis of their anticancer and antibacterial properties. The anticancer activity of ferrocenylvinylflavones 4-7 against established human cell lines derived from hematol. and solid tumors was evaluated in vitro. The following cell lines were studied: MCF-7 (estrogen receptor-responsive breast adenocarcinoma), MDA-MB-231 (estrogen receptor-neg. breast adenocarcinoma), HepG2 (hepatocellular carcinoma) and CCRF-CEM (T lymphoblast-like polymorph cells). All studied ferrocenylvinylflavones show cytotoxicity against CCRF-CEM cell line. The antibacterial activity of the four ferrocenyl-flavones against Gram-pos. methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA), vancomycin-resistant S. aureus (VRSA) and Staphylococcus epidermidis bacterial strains was detd. The authors' expts. show antibacterial activity for the carboxylic acid deriv. 7 against all tested Gram-pos. bacterial strains while no activity was detected for the ferrocene-free 6-bromo-chromen-4-one-3-propionic acid. [on SciFinder(R)]
Keywords: crystal structure ferrocenylvinylflavone prepn bactericide anticancer prepn electrochem